Norepinephrine and Epinephrine Enhanced the Infectivity of Enterovirus 71 - Liao, Yu-Ting (PLoS One, 2015)
BACKGROUND: Enterovirus 71 (EV71) infections may be associated with neurological complications, including brainstem encephalitis (BE). Severe EV71 BE may be complicated with autonomic nervous system (ANS) dysregulation and/or pulmonary edema (PE). ANS dysregulation is related to the overactivation of the sympathetic nervous system, which results from catecholamine release. OBJECTIVE: The aims of this study were to explore the effects of catecholamines on severe EV71 infection and to investigate the changes in the percentages of EV71-infected cells, virus titer, and cytokine production on the involvement of catecholamines. STUDY DESIGN: Plasma levels of norepinephrine (NE) and epinephrine (EP) in EV71-infected patients were measured using an enzyme-linked immunoassay. The expression of adrenergic receptors (ADRs) on RD, A549, SK-N-SH, THP-1, Jurkat and human peripheral blood mononuclear cells (hPBMCs) were detected using flow cytometry. The percentages of EV71-infected cells, virus titer, and cytokine production were investigated after treatment with NE and EP. RESULTS: The plasma levels of NE and EP were significantly higher in EV71-infected patients with ANS dysregulation and PE than in controls. Both α(1A)- and β(2)-ADRs were expressed on A549, RD, SK-N-SH, HL-60, THP-1, Jurkat cells and hPBMCs. NE treatment elevated the percentages of EV71-infected cells to 62.9% and 22.7% in THP-1 and Jurkat cells, respectively. Via treatment with EP, the percentages of EV71-infected cells were increased to 64.6% and 26.9% in THP-1 and Jurkat cells. The percentage of EV71-infected cells increased upon NE or EP treatment while the α- and β-blockers reduced the percentages of EV71-infected cells with NE or EP treatment. At least two-fold increase in virus titer was observed in EV71-infected A549, SK-N-SH and hPBMCs after treatment with NE or EP. IL-6 production was enhanced in EV71-infected hPBMCs at a concentration of 10(2) pg/mL NE. CONCLUSION: The plasma levels of NE and EP elevated in EV71-infected patients with ANS dysregulation and PE. Both NE and EP enhanced the percentages of infected cells and virus titers in EV71 infection in vitro. NE and EP may play a role in the pathogenesis of EV71 BE complicated with ANS dysregulation and PE.